THAI BOYS’ LOVE: QUEER REPRESENTATION AND CULTURAL DIPLOMACY IN THAILAND’S SOFT POWER STRATEGY IN SOUTHEAST ASIA - Setiawan, Roy; Nyarimun, Ansgrasia Jenifer; Amalia, Naslika (BHUVANA: Journal of Global Studies, 2025)
Thai Boys’ Love has emerged as a powerful medium of cultural diplomacy, shaping Thailand’s image as a progressive and inclusive nation in Southeast Asia. This study examines how queer representation in Thai Boys’ Love is deployed as a tool of soft power in international relations. Using queer theory, media studies, and public diplomacy, the research explores the intersection of popular media narratives, regional reception, and cultural policy. The analysis focuses on three popular Thai Boys’ Love series: Love Sick, 2gether, and KinnPorsche, alongside an online survey of viewers in Indonesia and the Philippines. Findings reveal that queer representation in Thai Boys’ Love tends to be normative and aestheticized, featuring cisgender characters from urban middle-class backgrounds with personal conflicts. Digital distribution strategies and active regional fan communities have amplified the transnational reach of Thai Boys’ Love as a cultural product. This study concludes that Thai Boys’ Love functions as a form of cultural diplomacy, fostering emotional affiliation and positive perceptions of Thailand among regional audiences.